A Legal Review of Default in Online Loans in Indonesia - Made Indah Naraswari (Journal of Social Research, 2025)
This study discusses the regulation and legal protection of consumers in online lending practices (pinjol) in Indonesia, especially regarding the risk of default or failure to pay. The phenomenon of online loans is increasingly widespread, along with advances in digital technology and the increasing need for people to access funds quickly and easily. However, this convenience is often accompanied by the risk of high interest rates, unethical debt collection, and legal uncertainty, especially if the debtor is in default. The study aims to analyze the legal implications of online loan defaults in Indonesia, particularly focusing on the risks faced by borrowers when using unregistered online lending platforms. This study employs a normative legal approach, utilizing primary, secondary, and tertiary legal materials as data sources, which are analyzed qualitatively. The results of the study show that regulations regarding online loans have been regulated in various regulations, such as POJK No. 10/POJK.05/2022, SE OJK No. 19/2023, as well as the ITE Law, Consumer Protection Law, and Civil Code. However, even though regulations are available against illegal online lending practices. Therefore, it is necessary to strengthen rules, enforce stricter laws, and educate the public about the law to create a fair and safe online lending ecosystem for all parties.